The Role of Physical Education in the Development of Student Character in Schools - Carsiwan; Nadila Maesara; Maryati; Resty Sriayu Rahmadayanti (Indonesian Values and Character Education Journal, 2025)
Character refers to a set of moral values, attitudes, and behaviors that form an individual's personality and influence their actions across various situations. This study aims to analyze the contribution of physical education to character development in school students through a systematic literature review approach. The research followed the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses) protocol, utilizing the Covidence platform to facilitate the screening and data extraction process. Articles were retrieved from Google Scholar and Crossref databases using Harzing’s Publish or Perish application. Out of 750 initial articles, 15 met the established inclusion and exclusion criteria and were selected for systematic analysis. Thematic synthesis was applied to identify key findings across the studies. The results reveal that physical education plays a significant role in shaping students’ holistic character. Structured physical activities within the physical education curriculum can foster core values such as responsibility, cooperation, independence, discipline, tolerance, honesty, and self-confidence. The findings conclude that physical education not only supports physical development but also serves as a strategic medium for character reinforcement. This study offers important implications for curriculum development and learning practices that integrate character education through physical activities.